Stature Determination from 3D Foot Impression among Telugus in Malaysia - Nataraja Moorthy T; Sangitha J (Institute of Medico-legal Publications Pvt Ltd, 2021)
Personal identification is the primary aim of anyforensic investigations. Foot impressions, either 2D or 3Dare used for person identification. Foot impression found on soft surfaces is three dimension in nature (3D),also namedfoot outline which shows the boundaries of the foot left by the offenders on soft surfaces. It is afact that 3D impressions can also be used to determine stature, body weight and gender. In the developingcountries, people are still walking barefooted. Earlier foot impression studies were conducted on mixedpopulation and currently researchers are insisting the importance of ethnicity consideration.MalaysianIndians are an important ethnic group living in Malaysia, with minor sub-ethnicgroups such as Malayali,Telugu, Sikh, Tamil, and others. Hence this study intends to examine the relationship between stature and 3Dfoot lengths among Malaysian Telugus, mostly living in peninsular Malaysia. The stature and foot outlines(3D) were collected from consented Telugu 140 subjects, comprising 73 males and 67 females, age rangingfrom 18 to 60 years old. The data obtained were analysed statistically using SPSS software version 21.0.There exists a strong positive correlation between stature and 3D foot impression lengths and the correlationcoefficient (R) values are found to be higher in unknown gender/pooled samplefollowed by males andfemales. This study developed regression formulae to determine stature from foot outline (3D) lengthsamong Malaysian Telugus for crime scene investigation. The equations are population specific and shouldnot be used for any other populations.